2010
DOI: 10.1007/s00345-010-0603-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term urinary adverse effects of pelvic radiotherapy

Abstract: Objective Radiation for tumors arising in the pelvis has been utilized for over a 100 years. Adverse effects (AEs) of radiotherapy (RT) continue to accumulate with time and are reported to show decades after treatment. The benefit of RT for pelvic tumors is well described as is their acute AEs. Late AEs are less well described. The burden of treatment for the late AEs is large given the high utilization of RT. Review For prostate cancer, 37% of patients will receive radiation during the first 6 months after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 55 publications
3
45
0
2
Order By: Relevance
“…25 In studies with at least 3 years of follow-up, genitourinary toxicity rates are reported from 1.3% to 14.5%. 12 Although it is difficult to compare toxicity rates of this study to others given variation in cohort and outcomes measured, toxicity rates in this study were comparable to those previously reported.…”
Section: Discussionsupporting
confidence: 62%
“…25 In studies with at least 3 years of follow-up, genitourinary toxicity rates are reported from 1.3% to 14.5%. 12 Although it is difficult to compare toxicity rates of this study to others given variation in cohort and outcomes measured, toxicity rates in this study were comparable to those previously reported.…”
Section: Discussionsupporting
confidence: 62%
“…Although radiation effectively kills tumor cells, it also damages nearby healthy tissues. Radiotherapy for prostate cancer can cause severe long-term complications that include bowel and rectal wall damage, urinary urgency and frequency, erectile dysfunction, urethral stricture, and incontinence [3, 4]. Therefore, to improve radiation therapy-induced quality of life impairments, it is imperative to develop more effective therapies and innovative agents to protect normal tissues from radiation damage, while at the same time inhibiting tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we aimed to clarify the prognostic potential of the DCE-MRI Brix model parameters in patients with cervical cancer subjected to curative chemoradiotherapy and explore Authors' Affiliations: Departments of 1 Radiation Biology, 2 Medical Physics, 3 Gynecologic Oncology; 4 Institute for Medical Informatics; their molecular background by use of gene expression profiles. In a cohort of 78 patients, we carried out pharmacokinetic analyses of pretreatment DCE-MR images and generated parameter histograms of each tumor to account for the intratumor heterogeneity in physiologic conditions.…”
Section: Introductionmentioning
confidence: 99%